2017
DOI: 10.3892/or.2017.5955
|View full text |Cite
|
Sign up to set email alerts
|

MEK inhibitor, PD98059, promotes breast cancer cell migration by inducing β-catenin nuclear accumulation

Abstract: Abnormal activation of the RAF/MEK/ERK signaling pathway has been observed in breast cancer. Thus, a number of MEK inhibitors have been designed as one treatment option for breast cancer. Although some studies have found that these MEK inhibitors inhibit the growth of a variety of human cancer cells, some trials have shown that the use of MEK inhibitors as a treatment for breast cancer does not adequately improve survival for unknown reasons. In the present study, MEK inhibitor PD98059 was used to evaluate its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 45 publications
0
24
0
Order By: Relevance
“…During constant exposure to the drugs in the scratch wound assay, buparlisib inhibited cell migration more than trametinib. Interestingly, it has previously been shown that a MEK inhibitor was able to promote cell migration, despite drug-induced cell death in a dose-dependent manner [36]. Concerning the trans-well assay, measuring cell migration towards a chemoattractant, pre-treating cells with trametinib seemed to inhibit cell migration more than buparlisib.…”
Section: Discussionmentioning
confidence: 99%
“…During constant exposure to the drugs in the scratch wound assay, buparlisib inhibited cell migration more than trametinib. Interestingly, it has previously been shown that a MEK inhibitor was able to promote cell migration, despite drug-induced cell death in a dose-dependent manner [36]. Concerning the trans-well assay, measuring cell migration towards a chemoattractant, pre-treating cells with trametinib seemed to inhibit cell migration more than buparlisib.…”
Section: Discussionmentioning
confidence: 99%
“…EGFR usually performs its biological functions via activation of PLC‐γ1‐PKC, MAPK‐MEK‐ERK, and PI3K‐Akt‐mTOR signaling pathways (Lee et al, ; Huang et al, ). However, inhibition of these downstream pathway of EGFR often induces feedback activation of upstream multiple receptor tyrosine kinases (RTKs) and quick rebound of the pathway activity (Stratikopoulos et al, ; Zhao et al, ). Consistent with these reports, we found combination PI3K inhibitor LY294002 with tyrosine kinase inhibitor against EGFR produce an additive antiproliferative effect in breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The total proteins from cancer cells were extracted using RIPA buffer as previous described (Zhao et al, ). The nuclear protein was isolated using the nuclear protein extraction kit (Beyotime, Shanghai, China) according to the manufacturer's instruction.…”
Section: Methodsmentioning
confidence: 99%
“…The wound scratch assay was performed as previously described [17]. Cells were seeded in a 24-well plate and cultured, after cells had grown to confluence, a wound was scratched with a plastic tip and incubated for 24 h in RPMI 1640 medium.…”
Section: Methodsmentioning
confidence: 99%